A Study of Correlations between Chemical Composition, Hot Rolling Process Pa rameters, Microstructure and Mechanical Properties of Hot Rolled DP600 Steel - T. Kaźmierski; J. Krawczyk; Ł. Frocisz; P. Matusiewicz (Archives of Metallurgy and Materials)
DP600 steel is widely used in the automotive industry due to its exceptionally favourable combination of high tensile strength and good ductility. In the hot-rolling process, DP600 steel is produced by use of controlled cooling of the rolled strip from temperature above Ar3 to temperature below Ms. In this process, it is quite difficult to control key process parameters such as the time or temperature, and the final microstructure of the material is also affected by the degree of deformation of the material at various stages of the process. This paper presents a statistical analysis of the effect of chemical composition and selected hot rolling process parameters on the microstructure of DP600 sheet with respect to its mechanical properties. Based on industrial data from hot rolling mill combined with extended microstructure analysis, it was possible to find correlations between some of the analysed parameters and material properties. Among many correlations discussed in this work, most notable are those between martensite morphology and mechanical properties, between Mn and Si concentration and martensite morphology and between rolling speed, strain, cooling rate and mechanical properties.